2005
DOI: 10.1210/en.2005-0377
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glucokinase Activator Modulates Pancreatic Islet and Hepatocyte Function

Abstract: The glucose-sensing enzyme glucokinase (GK) plays a key role in glucose metabolism. We report here the effects of a novel glucokinase activator, LY2121260. The activator enhanced GK activity via binding to the allosteric site located in the hinge region of the enzyme. LY2121260 stimulated insulin secretion in a glucose-dependent manner in pancreatic beta-cells and increased glucose use in rat hepatocytes. In addition, incubation of beta-cells with the GK activator resulted in increased GK protein levels, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
134
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 29 publications
7
134
0
3
Order By: Relevance
“…Previous studies had revealed that induction of IRS2 results in improved glucose sensing and b-cell proliferation through enhancing insulin/IGF-1 signaling in islets [8,15]. Expression of PDX-1 and glucokinase was associated with glucose sensing and b-cell proliferation, respectively [7,11,12]. Thus, levels of PDX-1 and glucokinase mRNA were also measured in islets treated with herb extracts (Fig.…”
Section: Glucose-stimulated Insulin Secretion In Isletsmentioning
confidence: 85%
“…Previous studies had revealed that induction of IRS2 results in improved glucose sensing and b-cell proliferation through enhancing insulin/IGF-1 signaling in islets [8,15]. Expression of PDX-1 and glucokinase was associated with glucose sensing and b-cell proliferation, respectively [7,11,12]. Thus, levels of PDX-1 and glucokinase mRNA were also measured in islets treated with herb extracts (Fig.…”
Section: Glucose-stimulated Insulin Secretion In Isletsmentioning
confidence: 85%
“…GK plays an important role as a glucose sensor for controlling plasma glucose homeostasis by enhancing insulin secretion from pancreatic ␤-cells and glucose metabolism in the liver (1,2), which provides rational expectations that enhancement of GK activity would be a novel therapeutic strategy for type 2 diabetes. Consistent with this rationale, recently discovered small molecule allosteric activators of GK have been demonstrated to have antidiabetic efficacy in rodents (3,4).…”
mentioning
confidence: 85%
“…Since the report by Grimsby et al in 2003 [5], several glucokinase activators (GKAs) have been developed, and these have been shown to lower blood glucose in several animal models of type 2 diabetes [5][6][7][8][9][10][11][12]. In a study of beta cell function, it was reported that a GKA stimulated insulin secretion in a Ca 2+ -dependent manner in rodent islets and MIN6 cells [13], and we and others have reported that GKAs promoted beta cell proliferation and increased production of IRS2 [11,14], which is critically required for beta cell growth and survival [3,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%